Identification of highland peat vegetation in the Sub-district of Lintong Nihuta, Humbang Hasundutan Regency, North Sumatera, Indonesia. Issue 1 (November 2021) - Hutagaol, J M; Bintang,; Hidayat, B
Abstract: This study aims to identify the structure, composition, and current status of highland peat vegetation in the Lintong Nihuta Sub-district, Humbang Hasundutan Regency, North Sumatra Province. The research conducted from December 2020 to April 2021. This study uses a survey method. The plots were laid using the purposive sampling method considering that the observed plots were those with naturally growing vegetation and accessible terrain. Sampling used the double plot vegetation analysis method with a plot size of 4 x 4 m for seedlings and 20 x 20 m for saplings obtained by measuring the minimum area of the plot. The data obtained were analyzed for frequency calculations, important value index (IVI), and Shannon-Weiner diversity index (H'). The results of the vegetation analysis showed that from the four existing growth classes, only two growth classes were found at the research site, namely seedlings and saplings with a total of 23 species. The vegetation composition is dominated by shrub habitus which indicates that this peatland has been degraded. The dominant species in the study site were Lepinoria mucronata Rich. and Dicranopteris linearis (Burm.) F. Underw. The value of the biodiversity index (H') is 0.8 with a low criterion which means the vegetation ecosystem at the study site is unstable